2007
DOI: 10.1002/cncr.23089
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to independently verify the utility of the Van Nuys Prognostic Index for ductal carcinoma in situ

Abstract: BACKGROUND.The Van Nuys Prognostic Index (VNPI) purports to predict the risk of ipsilateral breast tumor recurrence (IBTR) after excision of ductal carcinoma in situ (DCIS). It is a simple scoring scheme based on a retrospective evaluation of data from a single group of investigators. Various versions of VNPI have been proposed using clinical and pathologic features including tumor size, tumor grade, margin width, and patient age. Despite common use of VNPI in the clinical management of patients with DCIS, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 52 publications
0
49
0
1
Order By: Relevance
“…However, with a median follow-up of 4.6 years, the results of the study by MacAusland et al 12 in 2007 did not agree with Silverstein's original results.…”
mentioning
confidence: 79%
“…However, with a median follow-up of 4.6 years, the results of the study by MacAusland et al 12 in 2007 did not agree with Silverstein's original results.…”
mentioning
confidence: 79%
“…However, this result should be weighed up against the 12% rate observed at 5 years in a series of low-risk patients (Wong et al, 2006). On the other hand, the Van Nuys Prognostic Index (VNPI), combining tumour size, grade and margin width, was used to select 'low-risk' patients not requiring RT (Silverstein et al, 1996), but was widely criticised in two large American and English studies including 222 and 237 patients, respectively (Boland et al, 2003;MacAusland et al, 2007). A recent Italian study (Di Saverio et al, 2008) including 259 patients also used VNPI and concluded in the absence of statistically significant advantage in the CS þ RT vs the CS group.…”
Section: Discussionmentioning
confidence: 99%
“…(37) Based on a retrospective analysis, this score has not been validated by other researchers. (38,39) The inclusion criteria of the RTOG 9804 study -mammographically detected DCIS, low or intermediate grade, ≤ 2.5 cm in size, resected margins negative at a minimum of 3 mm -now serve as the gold standard for defining low risk DCIS. (40) RTOG 9804 was a prospective randomized trial comparing RT with observation after BCS in patients with low risk DCIS.…”
Section: Selection Of "Good Risk" Patientsmentioning
confidence: 99%